2019
DOI: 10.1093/annonc/mdz009
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin and ESHAP is highly effective as second-line therapy for Hodgkin lymphoma patients (long-term results of a trial by the Spanish GELTAMO Group)

Abstract: Background: In this work, we assessed the efficacy and safety of brentuximab vedotin (BV) plus ESHAP (BRESHAP) as secondline therapy for Relapsed/Refractory Hodgkin lymphoma (RRHL) to improve the results before autologous stem-cell transplantation (ASCT).Patients and methods: This was a multicenter, open-label, phase I-II trial of patients with RRHL after first-line chemotherapy. Treatment had three 21-day cycles of etoposide, solumedrol, high-dose AraC, and cisplatin. BV was administered at three dose levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 33 publications
4
73
0
7
Order By: Relevance
“…These very encouraging results with BvB as well those reported with the association of Bv with other classic chemotherapeutics agents 44,45 and those with checkpoint inhibitors 46…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These very encouraging results with BvB as well those reported with the association of Bv with other classic chemotherapeutics agents 44,45 and those with checkpoint inhibitors 46…”
Section: Discussionsupporting
confidence: 71%
“…These very encouraging results with BvB as well those reported with the association of Bv with other classic chemotherapeutics agents and those with checkpoint inhibitors have opened new horizons in the treatment of patients with RR‐cHL . Due to the availability of diverse novel effective second‐line combinations for RR‐cHL, scientific efforts are required to identify the best algorithm for their timely use along with the natural history of the disease taking account of their efficacy and toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a phase 1/2 trial by Garcia‐Sanz et al investigated the addition of brentuximab vedotin (BV) to ESHAP in patients with relapsed or refractory cHL as induction therapy before planned ASCT. The combination showed improved efficacy when indirectly compared to ESHAP alone while still being tolerable . BV in combination with other chemotherapy agents (doxorubicin, vinblastine, and dacarbazine) also has already been shown to be superior to standard chemotherapy with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) in the frontline treatment of advanced HL in the ECHELON‐1 trial .…”
Section: Introductionmentioning
confidence: 98%
“…The combination showed improved efficacy when indirectly compared to ESHAP alone while still being tolerable. 6 BV in combination with other chemotherapy agents (doxorubicin, vinblastine, and dacarbazine) also has already been shown to be superior to standard chemotherapy with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) in the frontline treatment of advanced HL in the ECHELON-1 trial. 7 Two-phase 1/2 studies by LaCasce et al 8 and O'Connor et al 9 in 2018 showed that therapy with BV could achieve high CR rates as salvage therapy and was still effective in heavily pretreated patients, while having manageable side effects when indirectly compared to platinum-based therapies.…”
mentioning
confidence: 99%
“…as single-agent or in combination with chemotherapy either sequentially or concurrently (with augmented ICE/ICE, DHAP, ESHAP), reported ORRs of 68-75% and CRs of 35-50% for single agent therapy,[60][61][62] as well as ORRs ranging from 87-100% and CRs ranging from 70-100% with combination therapy 59,[63][64][65][66][67]. In addition, several recent studies have evaluated the use of brentuximab vedotin as first-salvage therapy for relapsed or refractory Hodgkin lymphoma in combination with bendamustine (as a potentially less toxic alternative to platinum-or gemcitabine-based chemotherapy),…”
mentioning
confidence: 99%